2015
DOI: 10.1021/acs.biomac.5b00336
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Hybrid Polymer/Lipid Expansile Nanoparticles: Imparting Surface Functionality for Targeting and Stability

Abstract: The size, drug loading, drug release kinetics, localization, biodistribution, and stability of a given polymeric nanoparticle (NP) system depend on the composition of the NP core as well as its surface properties. In this study, novel, pH-responsive, and lipid-coated NPs, which expand in size from a diameter of approximately 100 to 1000 nm in the presence of a mildly acidic pH environment, are synthesized and characterized. Specifically, a combined miniemulsion and free-radical polymerization method is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 81 publications
0
30
0
Order By: Relevance
“…We have previously shown that by modifying eNP -targeted) the rates of particle internalization can be tuned and, in particular, selectively increased in tumor-cell subtypes that overexpress the folate receptor [40]. However, surface modification can interfere with the pH functionality of the system and, for this reason, it was not employed in the current study [40].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have previously shown that by modifying eNP -targeted) the rates of particle internalization can be tuned and, in particular, selectively increased in tumor-cell subtypes that overexpress the folate receptor [40]. However, surface modification can interfere with the pH functionality of the system and, for this reason, it was not employed in the current study [40].…”
Section: Discussionmentioning
confidence: 95%
“…Surface charge is one of the factors that impacts nanoparticle internalization within cells (in addition to particle size, shape and stiffness), as has been described in a number of papers and reviews [35][36][37][38][39]. We have previously shown that by modifying eNP -targeted) the rates of particle internalization can be tuned and, in particular, selectively increased in tumor-cell subtypes that overexpress the folate receptor [40]. However, surface modification can interfere with the pH functionality of the system and, for this reason, it was not employed in the current study [40].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, due to the pH-responsive swelling functionality, where HFR-eNPs expand from ~30 to ~500 nm—described in detail in ref 45 and in refs 29, 31, 36, 42, and 46—the pH of the local microenvironment may play a role in the specificity of the HFR-eNPs for tumors. To determine the relationship of eNP localization and low-pH tumor microenvironments, we immunostained tissues for (1) HIF1 α as an indicator of cellular hypoxia and hypoxia-associated low pH and (2) lactate dehydrogenase-A (LDH-A) expression as an indicator of lowpH tumor microenvironments from the production of lactic acid.…”
Section: Resultsmentioning
confidence: 99%
“…The stability is an important factor for successful application of liposomes as drug carrier 32. It can be improved by adding PEG to the surface of the liposomes because PEG constitutes a hydrophilic layer surrounding the vesicles which may protect the liposomes from degradation or accelerated leakage 33 34.…”
Section: Discussionmentioning
confidence: 99%